Displacement of bilirubin from human albumin by drugs - Achmad Surjono Achmad Surjono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1986)
The displacing effect of 18 commonly used drugs on bilirubin-albumin binding were studied quantitatively. The competitive results of certain concentrations of drugs were measured by peroxidase oxidation method on standard bilirubin-albumin solution (bilirubin 0.255 mmol, albumin 0.45 mmol. bil /alb 0.56). Sulfisoxazole, the known clinically potent bilirubin-displacer was used as control. The apparent binding constant to the high-affinity site of albumin (Kd) of mephenamate (1.4 X 105), 'indomethacin (1.23 X 105), diflunisal (8.4 X 104), diazepam (6.7 X 104) and furosemide (3 X 104) were stronger than sulfisoxazole (1.72 x 104). Latamoxef, aminophylline and cefalotin were slightly lower than sulfisoxazole. The maximal displacing factors (MDF) were also determined, whereas sulfisoxasole was 2.29. Taking the MDF 1.2 as the upper limit for significant danger of displacement, mephenamate (4.02), latamoxed (1.63) and diflunisal (1.24) showed a higher risks Moderate to slight risks of displacement were recorded on indomethacin, cevalotine, cefotaxime, acetyl salicylic acid, aminophylline, phenobarbital, furosemide and ampicillin. No possible bilirubin-displacer were shown by sulir. idac, diazepam, doxapzam, digoxin, amikacin, gentamicin and kanamycin. Caution and substitution should be considered in giving non-steroid and-inflammatory drugs for closure of patent ductus arteriosus and latamoxef for sepsis in premature infants because of their potential risk of bilirubin encephalopathy. Key Words: albumin-bilirubin-binding drugs - displacing effect - kernicterusanti-inflam matory drugs - bilirubin encephalopathy